Government, Business and Lobbyists: The Politics of Palm Oil in US–Malaysia Relations - Yacob, Shakila (Taylor & Francis, 2019)
This paper reviews how information was utilised by the disputing parties made up of producers and consumer interests in seeking and opposing the imposition of tariff and non-tariff barriers relating to the entry of palm oil into the US market. Information was used in a variety of ways to mould public opinion and influence official US trade policy. Producers, with the support of the Government of Malaysia, countered US efforts by mounting an information-based counter-campaign. This study examines how US-based opponents to the importation of oil palm used information to influence consumer opinion and governmental decision-makers. It goes on to describe countermeasures taken by Malaysian producers. These latter measures included counter-arguments challenging spurious claims made by US-based groups. The paper also reviews the role played, and the positions taken by the US and Malaysian governments. Malaysia, as one of the world’s leading exporter of palm oil, reacted to preserve and protect the interests of various stakeholders in the palm oil industry. Measures taken included greater R&D effort, stronger trade promotion and countering spurious information. This study demonstrates how information was used by disputing parties to shape consumer opinion and develop a case for policy intervention by the respective governments. © 2018 Informa UK Limited, trading as Taylor & Francis Group.